Case report: Pseudoprogression mimicking neoplastic recurrence three months after completion of proton beam therapy for an IDH-mutant astrocytoma CNS WHO grade 3 - Heggebø, Liv Cathrine; Borgen, Ida Maria Henriksen; Blakstad, Hanne; Saxhaug, Cathrine; Rønning, Pål André; Niehusmann, Pitt Frederik; Werlenius, Katja; Blomstrand, Malin; Brandal, Petter (Frontiers in Oncology, 2025)
BackgroundRadiation-induced changes following proton beam therapy in isocitrate dehydrogenase (IDH)-mutated diffuse central nervous system (CNS) World Health Organization (WHO) grade 2 and 3 gliomas are not well characterized. We present a patient with an IDH-mutant astrocytoma CNS WHO grade 3 treated with proton beam therapy and with postradiation MRI changes suggestive of neoplastic progression that surprisingly turned out to be reactive.Case presentationA man in his twenties underwent surgery with a near gross total resection for what turned out to be an IDH-mutant astrocytoma CNS WHO grade 3. He was included in the PRO-GLIO trial and randomized to receive proton beam therapy to a total dose of 59.4 Gray (Gy) relative biological effectiveness (RBE). Four weeks after completion of radiotherapy, adjuvant temozolomide was commenced. All treatment was well tolerated, and the patient was in excellent general condition. Surprisingly, magnetic resonance imaging (MRI) examination three months after completion of radiotherapy showed what was highly suggestive of a distant recurrence. The patient underwent resective surgery about seven months after his first surgery. Histological examination showed inflammatory changes without neoplastic tissue, albeit not very typical for postradiation changes. Adjuvant chemotherapy with temozolomide was continued.ConclusionThe presented case clearly shows that caution must be taken when interpreting cerebral MRI changes postradiation, and in particular after proton therapy. Further understanding of this subject is crucial to distinguish between patients requiring intensified antineoplastic treatment and those for whom maintaining current therapy or ongoing watchful waiting is advisable.